Long Term Outcome of 112 Pediatric Patients With Ureteroplevic Junction Obstruction Treated by Endourologic Retrograde Balloon Dilatation - Javier Ordóñez; Rubén Ortiz; Alberto Parente; Laura Burgos; Beatriz Fernández-Bautista; Laura Pérez-Egido; José María Angulo (Frontiers Media S.A., 2022)
PurposeTo analyze the effectiveness, complications and long-term outcome of the patients with ureteropelvic junction obstruction (UPJO) treated by endoscopic retrograde balloon dilatation (ERBD) in the largest series reported.Materials and MethodsBetween years 2004 and 2018, 112 patients with primary unilateral UPJO were treated by ERBD. Endoscopic treatment consisted on a retrograde balloon dilatation of the ureteropelvic junction (UPJ), through cystoscopy and under fluoroscopic guidance, using high-pressure balloon catheters. In case of persistence in the balloon notch, a Cutting Balloon™ catheter was used. Double-J stent was placed after dilatation.ResultsMean age at surgery was 13.1 ± 21.3 months, 92 cases being younger than 18 months. Mean operative time was 24.4 ± 10.3 min; hospital stay was 1 day in 82% of patients. No intraoperative complications occurred. UPJ was calibrated at time of stent removal with cystoscopy 39.1 ± 13.7 days after dilatation. ERBD was not possible in 11 cases. An additional procedure was needed in 24 cases: second ERBD (n = 11, seven during the stent withdrawal), a third dilatation (n = 3) due to persistent hydronephrosis, and percutaneous endopyelotomy (n = 3) or open pyeloplasty (n = 7) in cases of technical failure. Significant improvement in postoperative ultrasound measures were observed (p < 0.05, T-test). Long-term success rate was 76.8% after one dilatation, and 86.6% in those who required up to 2 dilatations. Mean follow-up was 66.7 ± 37.5 months.ConclusionsERBD is a feasible and safe option for the minimally invasive treatment of UPJ obstruction in infants. Long-term outcome is acceptable with a very low complication rate.